Resource Dependence and Fiscal Effort in Sub-Saharan Africa - Thomas, Alun (IMF Working Papers; Working Paper, 2013)
High natural resource prices in recent years have resulted in sizeable increases in fiscal revenue for many resource-exporting countries in sub-Saharan Africa. However, this revenue source is volatile, and arguably these countries should also rely on other forms of taxation to help fund public expenditure. This paper asks whether the availability of higher resource revenue in these countries has led to lower taxation effort of other revenue categories. The question is analyzed both in terms of the relationship between non-resource tax revenue and resource revenue, and between non-resource tax revenue and statutory tax rates. The paper finds evidence suggesting that nonresource revenue is negatively influenced by a higher resource revenue-to-GDP ratio. The lower take up of nonresource taxes in resource-rich countries is correlated with higher levels of corruption in these countries, suggesting weaker institutions affect nonresource revenue through incentives for tax evasion and/or large tax exemptions as argued in the literature.